Study on the structure characterization and swelling properties of the Fe3O4/CMS composite membrane - Liu, Xiaokai (Environmental technology, 2024)
In order to improve the functionality of cellulosic materials research and development of high performance soluble materials. Therefore, the Fe3O4/CMS composite membrane was prepared by using carboxymethyl salix powder (CMS) and Fe3O4 as raw materials, 1-propenyl-3-methylimidazolium chloride and dimethyl sulfoxide as dissolution system. The effects of swelling time, swelling temperature, pH and ionic strength on the swelling performance of Fe3O4/CMS composite membranes and the swelling kinetics of the composite membranes were studied. The structure of the composite membrane was characterized by SEM, FT-IR, XRD and TG. The results showed that the swelling degree reached 5.54 g·g-1, when the swelling time was 45 min, the swelling temperature was 65°C, the pH was 5 and the ionic strength was 0.08 mol·L-1. The initial phase of dissolution of the composite membrane fits well with the Fickian diffusion model, and the whole dissolution process belongs to the Schott model, indicating that the main role of the dissolution process is the diffusion of water molecules, while the composite membrane can be preserved for a long time at high temperature, which provides sustainability for the composite membrane. The characterization results showed that the surface of Fe3O4/CMS composite film was rough with small grooves. The O-H effect was enhanced and the Fe-O absorption peak appeared at 600 cm-1, indicating that Fe3O4 had been successfully loaded onto the cellulose membrane. The Fe3O4/CMS composite membrane belonged to cellulose type II structure, meanwhile, the composite membrane had good thermal stability